1992
DOI: 10.1161/01.str.23.10.1504
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-associated alterations in ischemic brain metabolism of neonatal piglets.

Abstract: Background and Purpose: During global brain ischemia or hypoxia-ischemia in adults, hyperglycemia is deleterious to the brain. In contrast, similar adverse effects have not been found in neonatal animals. This investigation examined neonatal piglets to determine if there were specific alterations of ischemic brain metabolism associated with different systemic glucose concentrations and to potentially clarify the effects of hyperglycemia during ischemia in neonates.Methods: Two groups of animals (n=12 in each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 42 publications
1
12
0
3
Order By: Relevance
“…This finding is consistent with previous studies in newbo rn animals that demonstrated that hyperglycemia either had no significant effect on the cereb ral response to hypoxia/ischemia (13,29) or improved outcome as indicated by improved surviva l (16,30) or decreased infarct size (31). In contra st, severa l studi es of cerebral hypoxia/ischemi a in adult animals found that hyperglycemia during or after the insult is associated with decre ased survival (32,33), signific ant increases in cereb ral lactate concentration, and reduced intracellular pH (7,9), as well as more extensive neuronal necros is and infarct size (4,33,34).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies in newbo rn animals that demonstrated that hyperglycemia either had no significant effect on the cereb ral response to hypoxia/ischemia (13,29) or improved outcome as indicated by improved surviva l (16,30) or decreased infarct size (31). In contra st, severa l studi es of cerebral hypoxia/ischemi a in adult animals found that hyperglycemia during or after the insult is associated with decre ased survival (32,33), signific ant increases in cereb ral lactate concentration, and reduced intracellular pH (7,9), as well as more extensive neuronal necros is and infarct size (4,33,34).…”
Section: Discussionsupporting
confidence: 93%
“…In the newborn, the effect of decreased substrate availability with subsequent energy depletion may be more critical than the accumulation of lactate and development of tissue acidosis (17). Hyperglycemia may be associated with better preservation of levels of high-energy phosphates during hypoxia/ischemia in both adults (37) and newborns (29), although Wagn er et al (4) found no difference in ATP levels during ischemia in hyperglycemic versus normoglycemic adult cats. The study design used in the present investigation precluded measurement of the effect of hyperglycemia on preservation of cerebral levels of high-en ergy phosphates during hypoxia, inasmuch as FiO z was adjusted to produce comparabl e reduction s in PCr in untreated and hypergl ycemic animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, hyperglycemia has been shown in numerous studies to exacerbate ischemic damage (12)(13)(14)(15)(16). Because hyperglycemia also increases intraischemic lactic acid levels (27)(28)(29), it was reasonable to conclude that lactic acidosis itself exacerbates the ischemic brain damage during hyperglycemia. However, the role of glucose in brain injury in the adult as well as juvenile or fetal animals is far from resolved because many studies have failed to show detrimental effects resulting from glucose infusions and some have even shown beneficial effects of preischemic glucose infusions both in vitro (53)(54)(55)(56) and in vivo (21, 22, 31-33, 57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that hyperglycemia in conjunction with hypoxic/ischemic episodes in piglets accentuates the decreases in brain pH, increases in the production of lactate and lipid peroxidation products, and increases pathologic damage (27)(28)(29). In exteriorized asphyxiated fetal sheep, hyperglycemia was associated with reduced cerebral oxygen consumption and deterioration of the somatosensory evoked potentials (24) and in the newborn dog, hyperglycemia accentuated brain damage in select brain regions (30).…”
mentioning
confidence: 99%
“…Для поддержания мозгового кровотока происходит перераспределение гемодинамики с увеличением кровоснабжения сердца и головного мозга за счет подъема АД вследствие повышенного выброса адреналина и норадреналина (катехоламиновый всплеск) [5][6]. Глюкоза и кислород являются основными субстратами питания мозга.…”
Section: Introductionunclassified